Bibliometric analysis and visualized study of research on autophagy in ischemic stroke - Chen, Jiefang; Chen, Gaijie; Xu, Xiaojing; Chen, Long; Zhang, Jiewen; Liu, Feng (Frontiers in Pharmacology, 2023)
Aims: To summarize and clarify the current research status and indicate possible future directions in the field of autophagy in ischemic stroke, we performed a comprehensive and multidimensional bibliometric analysis of the literature in this field published from 2011 to 2022. Methods: We retrieved articles on the field of autophagy in ischemic stroke published between 2011 and 2022 from Web of Science Core Collection (WOSCC). VOSviewer (version 1.6.19) and CiteSpace (version 6.2.R2 Basic) were used to identify the leading topics as well as generate visual maps of Countries/regions, organizations, authors, journals, and keyword networks in the related field. Results: A total of 568 publications were contained in this research. The journal with the most publications were Front Pharmacol, Mol Neurobiol, and Neuroscience. China was the most productive country with respect to co-authorship, with the Capital Med Univ being the organization with the most co-authorships. In terms of authorship analysis, eight of the top 10 most contributive authors were from China. The co-occurring author keywords can be divided into three main clusters, including “protective effect of autophagy in ischemic stroke”, “autophagy-targeted therapy for ischemic stroke”, and “mitochondrial function in cerebral ischemia-reperfusion injury”. Conclusions: This bibliometric analysis helps us reveal the current research hotspots in the research field of autophagy in ischemic stroke and guide future research directions. Subsequent trends in this special field are likely to identify and develop novel autophagy-targeted therapy strategies to effectively prevent and treat ischemic stroke.